Behind the scenes of the telecommunications miracle: An empirical analysis of the Indian market - Sara Biancini (Center for Economic Studies and ifo Institute (CESifo), 2010)
We analyze the demand and supply characteristics of the Indian telecommunications market, in order to assess the potential effectiveness of universal access policies in developing countries. We provide some empirical evidence on the supply and demand characteristics, using a small time-series-cross-section dataset on Indian States. We suggest that the price elasticity of demand for mainlines might be sensibly higher than the levels usually found in developed countries, while the crucial role of income and other sociodemographic variables seems to be confirmed. We also study the impact of cellular penetration, identifying a (positive) network effect in low penetration areas and some evidence of substitution (displacement) in the most developed ones. We finally analyze the supply side of the market, trying to assess the impact of market competition on investment: competition seemingly helps stimulating investment in the most developed areas, but has probably no significant impact in the less developed ones.
Keywords: L96; L51; O12; 330; telecommunications demand; universal service; competition; developing countries; India; Telekommunikationspolitik; Telekommunikation; Angebot; Nachfrage; Entwicklungsländer; Indien